Dynamics of microbial residues in highland agroecosystems as affected by cropping systems and fertilisation in a 31‐year‐long experiment. (29th December 2021) - Su, Fuyuan; Chen, Xu; Zhang, Liqiong; Hao, Mingde; Wei, Xiaorong
Abstract: Microbial residues are essential for soil organic carbon (SOC) accumulation and stability. However, the interactive effects of cropping system and fertilisation on microbial residues and their contributions to SOC have not been addressed. Herein, we used amino sugars as tracers for microbial residues and analysed the dynamics of microbial residues in a 31‐year‐long experiment in a highland agroecosystem to understand how effects of fertilisation vary with cropping systems. The cropping systems included continuous alfalfa (AC, a pure legume system), continuous winter wheat (WC, a non‐legume system) and grain‐legume rotation (GLR) system. The fertilization treatments were the unfertilised control (CK), phosphorus (P), P and nitrogen (NP) and NP and manure (NPM). When averaged across the experimental periods, compared with the GLR and WC systems, the AC system increased microbial residues, the ratio of fungal‐to‐bacterial residues and the contribution of fungal residues to SOC. The NP and NPM increased microbial residues, and the effects of NPM were greater than those of NP. However, the contribution of microbial residues to SOC was lower in the NPM treatment than that in the NP treatment. The effects of NP or NPM on microbial residues were similar among cropping systems, while the effect of P was greater in the AC system but smaller in the WC system in comparison with those in the GLR system. Therefore, the pure legume cropping system was conducive to SOC accumulation mainly by increasing fungal residues in soils. Manure combined with chemical fertilisers was more beneficial to the accumulation of microbial residues, but SOC accumulation caused by it was less attributable to the increase in microbial‐derived C. Moreover, P fertiliser was crucial for the accumulation of microbial residues in legume‐included cropping systems. Highlights: This study addresses effects of fertilization on microbial residues in three cropping systems. The effects of NP or NPM on microbial residues were similar among cropping systems. The effect of P fertilizer on microbial residues varied with cropping system. Legume cropping system was conducive to SOC accumulation mainly by increasing fungal residues.